Chloroform upregulates early growth response‐1‐dependent thymic stromal lymphopoietin expression via the JNK and ERK pathways in human keratinocytes. (16th October 2015) - Lee, Hana; Bae, Hyun Cheol; Kim, Jinhee; Jeong, Sang Hoon; Ryu, Woo‐In; Son, Sang Wook
Abstract: Background: Exposure to volatile organic compounds (VOCs) in the environment has been reported to exacerbate allergic inflammatory diseases, such as atopic dermatitis (AD). However, the exact mechanism by which VOCs induce an inflammatory response in the skin is poorly understood. Thymic stromal lymphopoietin (TSLP) is known to be an important factor in the initiation and maintenance of allergic inflammatory diseases, including AD. Objectives: The aim of this work is to define the correlation between VOCs and TSLP. Methods: The present study demonstrates dose‐dependent increases of TSLP protein and mRNA levels in keratinocytes following exposure to chloroform. We further investigated the regulatory mechanisms of chloroform‐induced TSLP expression in human keratinocytes. Results: Chloroform induces early growth response‐1 (Egr‐1) protein expression in human keratinocytes. This process is mediated by the c‐JUN N‐terminal kinase (JNK) and extracellular signal‐regulated kinase (ERK) signaling pathways. Inhibition of phosphorylated JNK and ERK significantly downregulated Egr‐1 expression, which was subsequently associated with reduced TSLP expression in chloroform‐exposed human keratinocytes. Moreover, treatment of Egr‐1 siRNA abolished chloroform‐induced TSLP protein expression and TSLP promoter transcriptional activation. Conclusions: Taken together, these findings suggest that, in human keratinocytes, the upregulation of TSLP by chloroform is induced through an Egr‐1‐dependent mechanism that requires the c‐JNK and ERK pathways. Our results suggest that exposure to chloroform may aggravate allergic skin diseases such as AD through Egr‐1‐dependent TSLP regulation.